Efficiency of syringe irrigation in chemomechanical root canal treatment - Alexandru Andrei Iliescu; Cristina Coralia Nistor; Irina Maria Gheorghiu; Sinziana Adina Scarlatescu; Iulia Roxana Marinescu; Ana Maria Zaharescu; Andrei Iliescu; Paula Perlea (Amaltea Medical Publishing House, 2023)
Syringe irrigation is still the most shared clinical procedure for delivering endodontic irrigants. The shape and size of apical preparation should be matched to the individual morphological profile of the root canal to perform adequate cleaning. The irrigant flow beyond the needle tip seems to be influenced by the flow rate rather than the individual intra-barrel pressure developed within syringe. Proper selected size of the irrigation needle adapted to corresponding apical preparation size and the multiple maneuvers of irrigation should result in an expected cleaning efficacy. Irrigant replacement, shear stress and apical pressure are crucial cleaning factors in mutual contradiction. Presently no consensus came out to establish to whom should be forwarded the main concern.